Soil assessment in Denmark: Towards soil functional mapping and beyond - Lucas Carvalho Gomes; Amélie Marie Beucher; Anders Bjørn Møller; Bo V. Iversen; Christen Duus Børgesen; Diana Vigah Adetsu; Gasper Laurent Sechu; Goswin Johann Heckrath; Julian Koch; Kabindra Adhikari; Maria Knadel; Mathieu Lamandé; et al. (Frontiers in Soil Science, 2023)
Soil provides essential ecosystem services sustaining and improving human life, but mapping soil functions is an ongoing challenge. Denmark has a long history of carrying out soil assessments − originally in order to determine tax revenues for the king, and, more recently, for aiding policymakers and farmers. This knowledge has supported the development of intensive agricultural systems while maintaining the provision of ecosystem services (e.g., clean water). Getting an overview of historical soil surveys and pedological mapping approaches can generate useful information for mapping soil, identifying gaps and proposing directions for future research. In this review, we explore the evolution of soil and environmental inventories, the historical development of soil mapping methods, and how these factors contributed to a better spatial understanding of soil functions. Specifically, we discuss soil functions related to water regulation (e.g., drainage, groundwater and water surface interactions, water table), water filtering (e.g., nitrogen leaching), carbon sequestration (e.g., peatlands), agricultural production (e.g., land suitability, wheat yields), and threats related to soil degradation (e.g., soil erosion). Denmark has benefitted from a government-coordinated approach, promoting detailed and systematic national soil surveys and environmental monitoring programmes. The large databases produced in the surveys formed the basis for mapping several soil properties and functions at increasingly high resolutions over the last many years based on developments in machine learning. In contrast to methodological advances in soil mapping and relevant contributions to pedometric research, we identified a lack of spatial information on soil biodiversity. Detailed spatial information about soil functions is essential to address global issues, such as climate change, food security and water security, and the experience of mapping soil functions in Denmark can be a source of inspiration to other parts of the world.